The Dynamics of Processing Knowledge in Citizen Science Projects. Enhancing Participation in Public Citizen Science Formats - Wyss, Eva L.; Saal, Jannik; Rapp, Andrea; Schmunk, Stefan; Dietz, Nadine; Dunkelmann, Lena; Korb, Nina; Naunheim, Anna (Citizen science : theory and practice, 2025)
Scientific practice has increasingly integrated participatory approaches, with citizen science (CS) serving as a prominent mode of engaging publics in knowledge production. Far from being merely instrumental, CS challenges traditional epistemic hierarchies by foregrounding the contributions of citizen participants — not only in data collection but also in shaping research agendas, methodologies, and interpretive frameworks. For those of us working within this paradigm, the focus has shifted from legitimising participation to critically examining its implication for authority, data quality, and the politics of knowledge. Through seminar-style meetings, CS collaborations in the humanities foster reciprocal exchange and mutual learning between researchers and participants. These forms can be further contextualised through Haklay’s (2013) scaled model of participation, which differentiates levels of citizen involvement — from crowdsourcing and distributed intelligence to more engaged forms such as participatory science and extreme citizen science, in which citizens are fully involved in problem definition and data interpretation. In the context of citizen humanities, such engagements not only offer insight into scholarly practices but also support participants in reflecting on and re-evaluating their own cultural heritage. Participants are thus not merely data providers but co-constructors of knowledge, engaging with core methodologies from the social sciences and humanities. Building on this premise, our paper situates the “Gruß & Kuss” project (G&K) as a case study of a humanities CS project, with a specific focus on the forms of communication that structure citizen engagement. Central to our sociolinguistic analysis is a newly developed interaction format: the Love Letter Roundtables. Designed to go beyond conventional science communication, this format invites participants to engage in focused, dialogic sessions on linguistic features of love letter writing. These Roundtables serve not only as platforms for dissemination but as spaces of co-theorisation, grounded in principles of epistemic reciprocity. To examine participation on a micro-analytical level, we draw on qualitative conversation analysis to investigate how knowledge is displayed, negotiated, and co-constructed in the interaction. Our analysis highlights how both citizen scientists and academic researchers adopt and respond to epistemic stances—that is, how speakers position themselves (and are positioned by others) with respect to knowledge claims. These epistemic displays emerge as key mechanisms through which participants collaboratively navigate expertise, and contribute to the ongoing production of situated knowledge within the project.